Tingkat Kepatuhan Pemeriksaan Tekanan Darah Tinggi Pada Lansia Penderita Hipertensi - Yunita Sari, Rima; Luklukaningsih, Zuyina; Solichati Rizqi, Amalia; Windarti, Mariana (Jurnal Surya, 2024)
Introduction: Hypertension is a non-communicable disease (NCD) which is a severe health problem. This disease is categorized as a silent disease because sufferers do not know they have hypertension before having their blood pressure checked. Checking blood pressure in the elderly, especially in blood pressure sufferers, is one of the routine treatments for preventing the severity of hypertension. And Compliance with blood pressure checks is an important factor in controlling the severity of hypertension. So it is important to check the level of compliance in the elderly. Methods: This research uses an observational approach with data presentation using quantitative descriptives. Checking blood pressure in elderly people with hypertension using a Tensimeter. The number of subjects in this study was 40 elderly people who suffered from hypertension. The level of complience will be checked using a likert scale. The research was conducted in Semangkak village, Klaten district. Results: The level of compliance in the poor category was 40%, in the fair category was 42.5 %, and in the high category was 17.5 %. Conclusion: Based on the results it shows that the level of compliance of elderly people with hypertension in carrying out blood pressure checks is on average in the medium and low categories Keywords: Compliance, Hypertension, Elderly